2014
DOI: 10.1080/0092623x.2014.935539
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics by Type of Hypersexuality Referral: A Quantitative Chart Review of 115 Consecutive Male Cases

Abstract: Hypersexuality remains an increasingly common but poorly understood patient complaint. Despite diversity in clinical presentations of patients referred for hypersexuality, the literature has maintained treatment approaches that are assumed to apply to the entire phenomenon. This approach has proven ineffective, despite its application over several decades. The present study used quantitative methods to examine demographic, mental health, and sexological correlates of common clinical subtypes of hypersexuality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 32 publications
1
25
0
7
Order By: Relevance
“…Previous studies (e.g., Klein, Schmidt, Turner, & Briken, 2015;Reid et al, 2011;Sutton, Stratton, Pytyck, Kolla, & Cantor, 2015) have demonstrated that older participants (i.e., 60 years or older) can experience hypersexuality; therefore, it was decided to include older participants in the present study. Participants reported their place of residence as the capital city (53.9%), county towns (15.3%), towns (21.4%), or villages (9.3%); their highest level of education as primary (2.7%), secondary (36.5%), and higher education (60.8%).…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%
“…Previous studies (e.g., Klein, Schmidt, Turner, & Briken, 2015;Reid et al, 2011;Sutton, Stratton, Pytyck, Kolla, & Cantor, 2015) have demonstrated that older participants (i.e., 60 years or older) can experience hypersexuality; therefore, it was decided to include older participants in the present study. Participants reported their place of residence as the capital city (53.9%), county towns (15.3%), towns (21.4%), or villages (9.3%); their highest level of education as primary (2.7%), secondary (36.5%), and higher education (60.8%).…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%
“…Historically, levels of impotence among young men have been 2% to 5% (Park et al, 2016). A range of recent studies are finding that 27% to 33% of young men age 18-40 years are having erectile difficulties and low libido rates with a real partner (Bronner & Ben-Zion, 2014;Klucken, Wehrum-Osinsky, Schweckendiek, Kruse, & Stark, 2016;Kühn & Gallinat, 2014;Mialon, Berchtold, Michaud, Gmel, & Suris, 2012;Pizzol, Bertoldo, & Foresta, 2015;Sutton, Stratton, Pytyck, Kolla, & Cantor, 2015), though not with internet pornography (Landripet & Štulhofer, 2015). Essentially, they have conditioned their brains to respond to images on a screen and not to real partners.…”
Section: Harm Minimization -Reducing Demand For Legal Pornographymentioning
confidence: 99%
“…Researchers have also linked IP use with arousal, attraction, and sexual performance problems, including difficulty orgasming and erectile dysfunction (ED) (Sutton, Stratton, Pytyck, Kolla, & Cantor, 2015;Wéry & Billieux, 2016;Voon et al, 2014, Porto, 2016, negative effects on partnered sex (Poulsen, Busby, & Galovan, 2013;Sun, Bridges, Johnason, & Ezzell, 2014), a need for stronger pornographic material (Wéry & Billieux, 2016), and a preference for using IP to achieve and maintain arousal rather than having sex with a partner (Sun, Miezan, Lee, & Shim, 2015). In the latter study, users with increased interest in degrading or extreme IP also had the greatest concerns about their sexual performance, penis size, and ability to sustain an erection (Sun et al, 2015), suggesting their IP use may have fueled a need for more extreme stimulation.…”
mentioning
confidence: 99%